S4D:5 Targeted next-generation sequencing suggests novel risk loci in juvenile onset systemic lupus erythematosus. (21st March 2018) - Sandling, J; Hultin Rosenberg, L; Farias, FHG; Alexsson, A; Leonard, D; Murén, E; Karlsson, Å; Mathioudaki, A; Ericsson, D; Pielberg, G; Meadows, J; Nordin, J; et al.
Abstract : Purpose: Childhood onset systemic lupus erythematosus (SLE) is associated with a more aggressive disease course and higher mortality risk than adult onset SLE. It has been suggested that juvenile onset SLE cases could have a more genetically determined disease. To identify genetic risk loci in juvenile onset SLE we performed targeted DNA resequencing in a cohort of Swedish SLE patients and control individuals. Methods: Coding and regulatory regions of 1853 genes selected from pathways involved in immunological diseases were resequenced in 958 patients with SLE and in 1030 healthy individuals. All patients fulfilled at least four ACR 1982 classification criteria for SLE. For 117 of the SLE patients the disease onset was at age 18 or younger, 105 of whom were women and 12 men. Capturing of the targeted genes was performed with a Roche NimbleGen custom-made liquid capture library followed by Illumina HiSeq2500 sequencing. 97 264 single nucleotide variants (SNVs) passed quality control and had a minor allele frequency of at least 1%. Results: Single variant case-control association analysis revealed that 40 SNVs were associated with juvenile onset SLE (false-discovery rate <5%). These 40 SNVs were enriched for missense variants (8% vs 1.8% for all SNPs) and were annotated to 15 genes. Two coding SNVs on chromosome 1q25 showed the strongest evidence of association with juvenile onset SLE (p-values<5E-08), one of which results in a predicted deleterious amino acid change. Interestingly, this association exceeded the signal from the human leukocyte antigen region on chromosome 6. Conclusion: Using targeted sequencing we have identified coding SNVs in novel candidate risk loci in juvenile onset SLE. Our finding suggests differences in the genetic risk for childhood and adult onset SLE and provides insight into the genetic aetiology of juvenile onset SLE.